PICA Salon: Refracted Reality - Slatter, Nicole; Slatter, Bruce (Australia Council for the Arts, 2020)
PICA is pleased to present the significant group show Refracted Reality, curated by Perth based curator and artist Anna Louise Richardson, as our annual PICA Salon exhibition. This year the PICA Salon offers a curated selection of responses to the window as a motif or metaphor, a physical barrier that speaks to broader concerns of duality and exchange. In this exhibition the artists’ works are the medium through which ideas pass and bend, echoing questions of privacy, representational fictions in a post-truth era and a renewed interest in both the intimacy and constrictions of interior space in the wake of mass self-isolation. Refracted Reality will explore the work of ten artists and collaborations whose practices frame the complexities of human nature as a vivid spectacle of truths. The artists make visible the chaos of the urban domestic, digital landscapes and social upheaval, but also balance this with scenes of imaginary gardens, introspective interiors and the sublime landscape. Refracted Reality seeks to create a space of shelter, inviting the viewer into intimate environments and private rituals that create a mirage of perspectives which explore alternative realities.